P032 NONINVASIVE BIOMARKERS FOR INFLAMMATORY BOWEL DISEASE MONITORING: DRAWBACKS AND POTENTIAL. (7th February 2019) - Perry, Courtney; Barrett, Terrence; Yadav, Abhijeet; Patel, Vihang; Hashim, Mahmoud A
Abstract: Background: Approximately 1.6 million Americans suffer from inflammatory bowel diseases (IBD); Ulcerative colitis (UC) and Crohn's disease (CD). The goal of IBD therapy is to induce deep remission characterized by resolution of both endoscopic and histologic abnormality. However, frequent endoscopy is not always feasible for disease monitoring, leaving physicians to rely on less invasive markers of disease activity. Currently available biomarkers C-Reactive Protein (CRP) and Fecal Calprotectin (FC) have demonstrated utility as markers of disease activity, but each test has limitations for diagnostic use in IBD. Methods: IBD patients were recruited at University of Kentucky prior to undergoing endoscopy. Patient medical information was collected prospectively from electronic medical records and logged in a secure database. Lab results such as C-reactive protein (CRP), Fecal Calprotectin (FC), serum albumin, and hemoglobin were tracked, as well as clinical scores such as CDAI and HBI. This data was compared with endoscopy and pathology reports to assess correllation with disease activity. Results: The mean CRP and FC levels in our patient population were 0.6 (Normal <1) and 607 (Normal <162), respectively. Fecal cal demonstrated greater sensitivity for diease activity (85%) when compared to CRP (60%). However, patient compliance with fecal calprotectin testing limited utility, as roughly 1/3 of our patients did not submit a stool sample. Alternatively, compliance with CRP testing in these patients was 97%. We found that patients with a diagnosis of UC were more likely to comply with stool testing than those with Crohns disease. Conclusion: Our data supports fecal calprotectin as the best non-invasive biomarker for IBD activity. It correlates well with endoscopic activity and mucosal inflammation, but compliance with testing limits its utility for healthcare providers. As the field moves towards using noninvasive biomarkers to assess for deep remission;further analysis must be done to evaluate barriers to testing and issues with compliance. Given the nearly 100% compliance with CRP testing in our patients, this suggests that the future of non-invasive biomarkers lies in peripheral blood monitoring. There is a need for development of additional blood biomarkers that exhibit high sensitivity and specificity for IBD.